Performance Analysis of 5G MIMO-OFDM Systems in Wireless Communications using Modified PTS Scheme - Gautam, Pooja; Jatav, Munna Lal (International Journal of Computer Sciences and Engineering, 2019)
Orthogonal frequency division multiplexing (OFDM) is one of such popular method for achieving this high information rate. OFDM has several advantages, but one of the main drawbacks is its high peak-to-average power ratio (PAPR). However, the challenging part is that most of the PAPR reduction schemes come with high computational complexity. Recent PAPR reduction techniques such as partial transmit sequence (PTS) has been considered as most popular for PAPR reduction. This research work explores to find a solution for the PAPR reduction by using PTS technique, which has been implemented by using sub-blocks partitioning. In sub-block partition consists of OFDM data frame which is partitioned into several sub-blocks. An adjacent partitioning (AP) method can be perceived as the best of the existing partitioning method when the cost and PAPR reduction performance are considered together. In this paper a new partial transmit sequence (PTS) technique, based on PTS with discrete wavelet transform (DWT) and discrete cosine transform (DCT) technique, for two antennas MIMO-OFDM system, is proposed which can achieve better PAPR performance at much less bit error rate (BER). Simulation results show that the proposed approach can reduce BER and achieve a better PAPR reduction compared to previous PTS technique.